Fundamental mechanisms of colorectal carcinogenesis - Pasz-Walczak, Grażyna; Jesionek-Kupnicka, Dorota; Kubiak, Robert; Kordek, Radzisław (Contemporary Oncology/Współczesna Onkologia, 2004)
At present it is thought that there are two basic schemes of pathogenesis of colorectal cancer, i.e. adenoma → carcinoma sequence and microsatellite instability. A cascade of mutations of oncogenes and suppressor genes connected with the sequence of normal mucosa → adenoma → carcinoma appears in carcinomas originating on the basis of adenoma. The succession and accumulation of particular mutations of genes is essential in this variant and is related to the subsequent stages of carcinogenesis. Mutations of the APC, K-ras and P53 genes and deletion of the long arm of chromosome 18 occur in these cases. They are observed in 50-70% of sporadic colorectal cancers. Instead, microsatellite instability occurs as a result of a mutation of one of so-called mismatch repair genes MSH2, MLH1, PMS1, PMS2, MSH3, MSH6 (GTBP). Mutations of MSH2 and MLH1 are responsible for 80% of cases of this disorder. A phenotype called microsatellite instability (MSI) connected with disturbances in monobasic to tetrabasic repetitive DNA sequences originates in consequence of these mutations. In colorectal carcinogenesis disturbances different from mutations called an epigenetic regulation are also taken into consideration. In the human, the fundamental epigenetic process is hypermethylation related to the loss of function of genes as a result of blocking their transcription. It was demonstrated that certain colorectal cancers originate on the basis of this epigenetic disorder. Hypermethylation was discovered among others in promoters of the following genes MLH1, P16, P14 and APC.